Simultaneous biosynthesis of bacterial polyhydroxybutyrate (PHB) and extracellular polymeric substances (EPS): Process optimization and Scale-up. (December 2021) - Kopperi, Harishankar; Amulya, K.; Venkata Mohan, S.
Highlights: Simultaneous production of EPS and PHB using Providencia Sp. strain. EPS and PHB yield were influenced by pH and carbon load. Optimised conditions yielded maximum of 3.92 g L -1 (EPS) and 2.62 g L -1 (PHB) The process was scaled upto 5 L batch reactor. Dual biopolymer production can lower manufacturing cost and enhance raw materials use. Abstract: Owing to their biodegradability and renewability, biopolymers are being employed in industrial and bio-medical sectors as sustainable alternatives to chemical based polymers. In the present study, isolated Providencia sp. depicted dual production of intra and extracellular biopolymers, polyhydroxybutyrate (PHB) and extracellular polymeric substances (EPS), respectively . The polymer production process was optimised by varying process parameters such as carbon load (20, 30 and 40 g L -1 ) and pH (6, 7 and 8) for enhancing PHB and EPS productivity. Maximum yield of both PHB (2.62 g L -1 ) and EPS (3.92 g L -1 ) was observed with carbon load of 30 g L -1 at pH 7. Scale-up studies were performed with optimized conditions and PHB and EPS production of 2.62 g L -1 and 3.91 g L -1, respectively was observed. The extracted EPS and PHB were characterized using FT-IR, FE-SEM-EDX, H 1 and C 13 NMR and fluorescence microscopy.